Adolescente em conflito com a lei, resiliência, valores humanos e suporte familiar: um estudo das representações sociais - Estevam, Ionara Dantas (2011)
Crime and urban violence, committed by adolescents have reached high levels of intensity and frequency, in recent years requiring a deep analysis of their causes which are characterized in common sense as complex and multifaceted, revealing problems of psychological, relational, political, social and economic orders. These difficulties require studies in order to formulate scientific understanding for their prevention and / or intervention. Based on those principles, the general objective of this thesis was to identify the social representations of institutionalized adolescents in conflict with the law, and not institutionalized adolescents who are not in conflict with the law, concerning adolescence, violence, future, as well as, the measurement of resilience, basic values and family support issues. This research was developed according to the theoretical Moscovician s social representations SR, and other theories that support the studies of resilience, human values and family support. It was a field study, characterized by a multimethod approach, which used a qualitative and quantitative methodology. The locus of research counted on a ressocialized institution referred to as deprivation of liberty (104 adolescents) and public schools (104 adolescents) located in the suburbs of João Pessoa, totaling 208 participants. Five instruments were used: Sociodemographic Questionnaire, Technique of Free Association of Words (TFAW) in which the obtained data were processed by software Tri- Deux-Mots (version 2.2), the Resilience Scale developed by Wagnild and Young (RS), the Basic Values Questionnaire developed by Gouveia (BVQ) and the Family Support Perception Inventory (FSPI). The data of these last three were processed by the software SPPS (version 15). The results of the Sociodemographic Questionnaire revealed that delinquent adolescents are deprived of their liberty for committing robbery, murder and drug trafficking. These adolescents have lower education compared to the group of non delinquent adolescents, having various types of family arrangements. The results of TFAW objectified representations of adolescence (stimulus 1) entertainment, gaming and dating; those terms are similar for both groups. of adolescents; violence (stimulus 2), the adolescents represented differently, compared to non delinquent group, anchoring it in social representations of economic and political orders, and the delinquent adolescents represented with objective expressions of violence such as killing, stealing, hitting, the future (stimulus 3) objectified representations of life changes for both groups of adolescents. The RS, the BVQ and the FSPI showed that delinquent adolescents are less resilient, have less family support and their human values are guided to the experimentation, existence, normative and supra-personal, compared to the non delinquent adolescents who are more resilient, have more family support, their human values are more oriented to achievement and social interaction. Based on the findings the parameters of family support, resilience and human values must be understood as strengthening psychosocial factors, which may be constructed in the families, in the ressocialized educational institutions and in the community.